Sanghuangporus sanghuang extract extended the lifespan and healthspan of Caenorhabditis elegans via DAF-16/SIR-2.1 - Dong, Zhenghan; Wang, Yachao; Hao, Cuiting; Cheng, Yuan; Guo, Xi; He, Yanyu; Shi, Yueyue; Wang, Shuang; Li, Yunqi; Shi, Wei (Frontiers in Pharmacology, 2023)
Sanghuangporus Sanghuang is a fungus species. As a traditional Chinese medicine, it is known for antitumor, antioxidant and anti-inflammatory properties. However, the antiaging effect of S.Sanghuang has not been deeply studied. In this study, the effects of Sanghuangporus Sanghuang extract (SSE) supernatants on the changes of nematode indicators were investigated. The results showed that different concentrations of SSE prolonged the lifespans of nematodes and substantially increased these by 26.41%. In addition, accumulations of lipofuscin were also visibly reduced. The treatment using SSE also played a role in increasing stress resistance, decreasing ROS accumulations and obesity, and enhancing the physique. RT–PCR analysis showed that the SSE treatment upregulated the transcription of daf-16, sir-2.1, daf-2, sod-3 and hsp-16.2, increased the expression of these genes in the insulin/IGF-1 signalling pathway and prolonged the lifespans of nematodes. This study reveals the new role of S.Sanghuang in promoting longevity and inhibiting stress and provides a theoretical basis for the application of S.Sanghuang in anti-ageing treatments.